2016
DOI: 10.1007/s11099-016-0215-9
|View full text |Cite
|
Sign up to set email alerts
|

Light dependence of carboxylation capacity for C<sub>3</sub> photosynthesis models

Abstract: C 3 photosynthesis at high light is often modeled by assuming limitation by the maximum capacity of Rubisco carboxylation (V Cmax ) at low CO 2 concentrations, by electron transport capacity (J max ) at higher CO 2 concentrations, and sometimes by triose-phosphate utilization rate at the highest CO 2 concentrations. Net photosynthetic rate (P N ) at lower light is often modeled simply by assuming that it becomes limited by electron transport (J). However, it is known that Rubisco can become deactivated at less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The uppermost fully expanded leaf on five replicate plants for each treatment was analyzed. The P N - C i response of quinoa is sensitive to light intensity [ 70 ]; therefore, a saturating PPFD of 2000 μmol m −2 s −1 was used. The concentration of [CO 2 ] within the leaf cuvette was lowered to 50 μmol mol −1 for 60 min to fully open stomata and remove any diffusive limitations to P N before [CO 2 ] was increased in stages every 3 to 4 min when P N had stabilized ([CO 2 ] steps: 50, 100, 200, 300, 400, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000 μmol mol −1 ) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The uppermost fully expanded leaf on five replicate plants for each treatment was analyzed. The P N - C i response of quinoa is sensitive to light intensity [ 70 ]; therefore, a saturating PPFD of 2000 μmol m −2 s −1 was used. The concentration of [CO 2 ] within the leaf cuvette was lowered to 50 μmol mol −1 for 60 min to fully open stomata and remove any diffusive limitations to P N before [CO 2 ] was increased in stages every 3 to 4 min when P N had stabilized ([CO 2 ] steps: 50, 100, 200, 300, 400, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000 μmol mol −1 ) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…and internal CO 2 concentrations above 800 µmol CO 2 mol -1 [ 43]. Historically, with genetic improvement in soybean crop, there have been considerable modifications in plant architecture components with the goal of improving mechanization efficiency principally on the height of insertion of pods.…”
Section: Solar Radiation Interception Carbon Fixation and Grain Yieldmentioning
confidence: 99%
“…Bunce [8] found that the initial slope of A vs. Ci curves, an in situ measure of Rubisco carboxylation capacity, decreased as PPFD decreased in the steady-state, in a range of C3 species measured, over a range of temperatures. The result was that the relative stimulation of A at elevated vs. ambient CO2 did not decrease as PPFD decreased, at any temperature [8]. At lower PPFD, it is often assumed that carboxylation capacity remains constant while electron transport rate decreases.…”
Section: Introductionmentioning
confidence: 99%
“…This primarily lowers A at higher C i (Figure 2) and would result in a smaller relative stimulation of A between a C i of 250 and 375 µmol mol −1 , for example [7]. However, the assumption of constant carboxylation capacity at lower PPFD is incorrect, in the steady-state [8]. Bunce [8] found that the initial slope of A vs. C i curves, an in situ measure of Rubisco carboxylation capacity, decreased as PPFD decreased in the steady-state, in a range of C 3 species measured, over a range of temperatures.…”
Section: Introductionmentioning
confidence: 99%